State-Mandated Nutrition, Physical Activity, and Screen Time Policies in Child Care Centers. Issue 3 (May 2018) - Chang-Martinez, Catherina; Ahmed, Nasar U.; Natale, Ruby A.; Messiah, Sarah E.
Background . The child care center (CCC) environment presents opportunities for healthy weight promotion in preschoolers. Our study examined the current state of CCC adherence to nutrition, physical activity, and screen time legislative regulations and the differences in their adherence by center socioeconomic position (SEP: low, middle, high) in Miami-Dade County. Method . In 34 CCC, we used the Environment and Policy Assessment and Observation tool to evaluate nutrition, physical activity, and screen time practices during 1-school day. Results . Twenty-five of the centers (73.5%) were participants of the Child and Adult Care Food Program. Almost 80% of the centers adhered to serving low-fat/fat-free milk to children older than 2 years. Only 34.5% served vegetables and 75.9% served whole fruits during meals/snacks. Ninety-four percent of the centers had quiet and active play incorporated into their daily routines. All centers adhered to the 2-hour screen time limit for children older than 2 years. Low- and middle-SEP centers fared better in the serving of fruits, vegetables, and low-fat/fat-free milk. The centers averaged 1 hour in outdoor play regardless of SEP. High-SEP centers had no TV or screen time during day of observation. Conclusion . CCC practices highlight opportunities for improvement in nutrition, physical activity, and screen time practices in the prevention of overweight in early childhood.